Globalization: Myth or Reality? (American Journal of Islam and Society, 1998)
Since the 1960s, the world has witnessed an increasing fragmentationof the production process across national boundaries; the emergence oftransnational (as opposed to multinational) corporations; the rise of newsocial movements; and heightened cross-border flows of capital andlabor. As a result of these developments, scholars and practitioners havesought to understand what has brought about these changes. Is globalizationthe culprit, or is it simply a myth? If globalization is a reality, whatdoes it entail and how does it affect the realms of economy, polityy andsociety? In Paul Hirst and Grahame Thompson’s Globalization inQuestion: The International Economy and the Possibilities ofGovernance (1 996); James H. Mittelman’s (Ed.) Globalization: CriticalReflections (1 996); and Malcolm Waters’ Globalization (1 999, the struggleto answer these questions and many others is undertaken.’This article critiques the major points presented by each author inregard to the questions asked above. Each author’s views on globalizationas it relates to the economy, the state, and culture will be examined.Furthermore, this article will show that while all three works have theirdrawbacks and shortcomings, it is recommended that each book be readto gain an understanding of the wide range of empirical and theoreticalperspectives on globalization. The conclusion will offer suggestions onareas requiring more in-depth inquiry.What Is Globalization?While Mittelman, as well as Hirst and Thompson, discuss globalizationprimarily in terms of economic processes, Waters sees globalizationas driven by social or cultural processes. According to him, globalizationis a “social process in which the constraints of geography on social andcultural arrangements recede and in which people become increasinglyaware that they are receding” (p. 3). Waters contends that in a truly ...